Evaluation of remote sensing techniques-based water quality monitoring for sustainable hydrological applications: an integrated FWZIC-VIKOR modelling approach - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2024)
Evaluation of remote sensing techniques-based water quality monitoring for sustainable hydrological applications: an integrated FWZIC-VIKOR modelling approach by Abdullah Hussein Abdullah Al-Amoodi